التعبير عن الزمن في اللغة العربية وتدريسه لغير الناطقين بها - ماسي، سافيئينج (شافعي) (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 1999)
This study, first analyzes the proper method of using tenses (Past,. Present-future and Imperative), nouns and adverbs in Arabic language. Second, it also explains the method of teaching and the problems inherited therein. Finally. it has designed some practical lessons for the ease of learning. The study concludes as follows: First. the verb in Arabic language whether in the past, present and future, or imperative, plays an important role in the way the expression is formulated. tn fact, it represents an important part in the manners of expression. This is because the tense will change in line with any change in the verb with the addition of some prepositions. Second, there are basically three tenses in Arabic language { Past, Present, and Future), but it can be converted to sixteen by taking into consideration the direction of the person intended. All these tenses have been put into practice in different kinds of sentences in Arabic. This is because the grammatical tense is the core of the context while the composition of the sentence represents the different kinds of context. Finally, there are several derivatives like present participle, passive participle, simile adjective, vetbal noun, and advetb which also constitute the means of expression in standard Arabic language.